Effects of user experience and method in the inflation of endotracheal tube pilot balloon on cuff pressure - Ozer, A. B.; Demirel, I.; Gunduz, G.; Erhan, O. L. (Wolters Kluwer Medknow Publications, 2013)
Context: Endotracheal tube cuff pressure (ETCP) is recommended to be maintained between 20-30 cm H2O limits. While insufficient inflation of ETC may cause aspirations, over-inflation of it may lead to damage in tracheal epithelium. Aims: We planned to investigate the effects of user experience and cuff pressure inflation method differences following endotracheal tube cuff pressure and complaints about it. Patients and Methods: Two hundred and fifty patients planned for general anaesthesia were included in this study. ETC was inflated by users with different experience according to leakage or pilot balloon palpation techniques. ETCPs were measured by manometer at three periods (5 and 60 minutes after endotracheal intubation, and before extubation). Complaints about it were recorded in post anaesthetic care unit and 24 hours postoperatively. Results: Though we found experience of user had significant effect on the ETCP regulations, we observed inflation methods did not have any effect. However we found ETCP was higher than normal range with experienced users. A correlation was observed between cuff pressure and anaesthesia duration with postoperative complaints. Conclusions: Our study concluded that the methods used do not have any significant advantage over one another. While ETC inflated at normal pressure increases as users experience increases, experience alone is not enough in adjusting ETCP. A manometer should be used in routine inflation of ETC instead of conventional methods. CP and anaesthesia duration have correlations with some postoperative complaints.
Keywords: Endotracheal tube cuff pressure; experience of user; inflation methods